Our Paradise Uzbekistan (Zien Journal of Social Sciences and Humanities, 2022)
After the collapse of the Soviet Union, the Central Asian states became in- dependent and tried to pursue their foreign policy free from Russian control. Uzbekistan is the only Central Asian state to pursue a proactive and independent foreign policy. Uzbekistan has higher regional power ambitions than the other Central Asian states. So what is preventing Uzbekistan from fulfilling its dream? It has the necessary subjective and objective prerequisites for this: military potential, a large and fairly homogeneous population, natural resources, favorable geographic location, U.S. support of its secular state, and the willingness of the latter to recognize its regional hegemony. However, the country continues to face several limitations that hinder its leading role. Despite its capabilities, it is not engaging wholeheartedly in regional integration and is hampered by its geographic location, water shortages, structural economic constraints, political problems, and fundamentalism issues.